2004
DOI: 10.1080/07853890410026025
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rheumatoid arthritis

Abstract: Both genetic and environmental factors contribute to the development of rheumatoid arthritis (RA). A long-term latent process often precedes the onset of arthritis. Hence, the ultimate causes of RA cannot be clarified by studying only the inflamed joints. Longitudinal studies focusing on risk factors are crucial in approaching the true aetiology. At present, most information gained from epidemiological studies is contradictory or vague. For instance, there is no consensus concerning the long-term effects of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 73 publications
(62 reference statements)
0
39
0
1
Order By: Relevance
“…According to one case-control study, much of the increased RA risk during the postpartum period seems to be associated with lactation. A possible explanation for the association with breastfeeding is its relationship with HPRL [82]. Studies of PRL levels in non-pregnant patients with RA have not consistently demonstrated elevated levels.…”
Section: Prolactin Rheumatoid Arthritis and Pregnancymentioning
confidence: 93%
“…According to one case-control study, much of the increased RA risk during the postpartum period seems to be associated with lactation. A possible explanation for the association with breastfeeding is its relationship with HPRL [82]. Studies of PRL levels in non-pregnant patients with RA have not consistently demonstrated elevated levels.…”
Section: Prolactin Rheumatoid Arthritis and Pregnancymentioning
confidence: 93%
“…No case-control difference in smoking was detected, but there is just a statement to this effect without further supporting information. Furthermore, rheumatoid arthritis has a known association with smoking [13]; (iii) a study from Ferrara, Italy [14], containing 104 cases and 150 controls which showed no significant difference for 'smoking and drinking in adolescence', but further details are not given; (iv) two positive studies from Spain with insufficient data for analysis as described above [6,7]; (v) a negative study from North England [2], already described; (vi) the initial study from Oxford [3], which was supplemented by a later publication [4].…”
Section: Search Methodsmentioning
confidence: 99%
“…Smoking is claimed to be linked to autoimmune disease, such as rheumatoid arthritis, systemic lupus erythematosis, Grave's disease and Crohn's disease [13,18]. Nicotine may increase blood Á brain permeability to allow entry of abnormal T cells, or tobacco smoke may poison the central myelin, as it does in tobacco amblyopia, possibly by elevation of blood levels of its metabolite, thiocyanate.…”
Section: Combinedmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The most important genetic risk factor for rheumatoid arthritis is the presence of HLA class II alleles which share the conserved amino acid sequence called the shared epitope. 8 These shared epitope residues constitute a part of the antigen-presenting binding site.…”
mentioning
confidence: 99%